Investigating the impacts of using a mobile interactive English learning system on the learning achievements and learning perceptions of student with different backgrounds. Issue 1 (27th January 2022) - Cheng, Ching-Hsue; Chen, Chung-Hsi
Abstract: Many scholars have highlighted the importance of motivation and anxiety in language learning. They have also indicated the advantages of integrating learning content into a mobile-assisted English learning system environment. Meanwhile, a few studies have explored the impacts of a mobile-assisted English learning system on the motivation and English anxiety of elementary school students. This study explores these factors in the English learning achievement of elementary school students by using a mobile-assisted English learning system that includes interesting and interactive games. This study also tries to improve students' learning motivations and decrease their English anxiety through the mobile-assisted English learning system. This quasi-experimental design required 6 weeks to collect the data from the participants. A total of 79 students participated in the experiment, and they were divided into an experimental group and a control group. The students in the experimental group used a mobile-assisted English learning system to learn. Then, they filled out a questionnaire and evaluated whether the system's operations and their motivation, English anxiety, and perceived usefulness affected their learning achievement. The experimental results indicate that the mobile-assisted English learning system benefits students' learning achievement. Moreover, students with lower levels of English anxiety have better learning achievement than those with higher levels of English anxiety, and higher levels of perceived usefulness result in better learning achievement. These findings could be used as a reference for relevant instructors to find better assisted learning tools and improve students' learning achievement.